Covalent Triazine Framework Anchored with Co3O4 Nanoparticles for Efficient Oxygen Reduction. Issue 4 (5th January 2018) - Chen, Sicong; Zhu, Yuanzhi; Xu, Danyun; Peng, Wenchao; Li, Yang; Zhang, Guoliang; Zhang, Fengbao; Fan, Xiaobin
Abstract: The oxygen reduction reaction (ORR) is an important process in energy conversion and storage devices. Great efforts have been focused on developing efficient, durable, and low‐cost non‐Pt catalysts. In this study, a novel hybrid ORR catalyst of Co3 O4 and covalent triazine framework (CTF) was prepared through the in‐situ growth of Co3 O4 nanoparticles on CTF by using a hydrothermal method. Systematical studies revealed that this hybrid catalyst not only has a synergistic catalytic effect in the ORR, but also has superior stability and better methanol resistance than commercial Pt/C catalysts. Abstract : Let's synergize ORR : A novel hybrid catalyst of Co3 O4 and covalent triazine framework (CTF) is prepared through the in situ growth of Co3 O4 nanoparticles on CTF by using a hydrothermal method. This novel oxygen reduction reaction (ORR) catalyst shows a synergistic catalytic effect as well as comparable activity to the commercial Pt/C ORR catalyst (see picture).